Seismic tomography of the Pacific slab edge under Kamchatka - Jiang Guoming; Zhao Dapeng; Zhang Guibin (My University, 2009)
We determine a 3-D P-wave velocity structure of the mantle down to 700 km depth under the Kamchatka peninsula using 678 P-wave arrival times collected from digital seismograms of 75 teleseismic events recorded by 15 portable seismic stations and 1 permanent station in Kamchatka. The subducting Pacific slab is imaged clearly that is visible in the upper mantle and extends below the 660-km discontinuity under southern Kamchatka, while it shortens toward the north and terminates near the Aleutian–Kamchatka junction. Low-velocity anomalies are visible beneath northern Kamchatka and under the junction, which are interpreted as asthenospheric flow. A gap model without remnant slab fragment is proposed to interpret the main feature of high-V anomalies. Combining our tomographic results with other geological and geophysical evidences, we consider that the slab loss may be induced by the friction with surrounding asthenosphere as the Pacific plate rotated clockwise at about 30 Ma ago, and then it was enlarged by the slab-edge pinch-off by the asthenospheric flow and the presence of Meiji seamounts. As a result, the slab loss and the subducted Meiji seamounts have jointly caused the Pacific plate to subduct under Kamchatka with a lower dip angle near the junction, which made the Sheveluch and Klyuchevskoy volcanoes shift westward.
Keywords: 37.31.19 Сейсмология; Шивелуч; Ключевской